Childhood cancer in El Salvador: A preliminary exploration of parental concerns in the abandonment of treatment. Issue 4 (August 2015) - Rossell, Nuria; Gigengack, Roy; Blume, Stuart
Abstract Purpose In El Salvador, children under 12 diagnosed with cancer have access to free treatment at a specialized national facility. Until recently, 13 percent of patients annually abandoned therapy—a serious loss of lives and scarce resources. This qualitative study explores how some parents perceived their child's cancer and treatment, and what led them to stop bringing their child for chemotherapy. Method In in-depth interviews, parents of six children who abandoned their child's cancer treatment discussed sickness and life circumstances during the course of treatment. Results Poverty, effects of treatment, mistrust, emotions and religious convictions all figured in the parents' explanation of their actions. However, each family weighed these concerns differently. It was the interaction of the concerns, and not the concern per se, that represented the explanatory frameworks the families used to explain stopping their child's treatment. This finding illustrates the parents' navigation among a collection of variable concerns, rather than exposing one fixed cause for their behavior. For example, poverty affects a parent's worldview as well as concrete living conditions, and therefore has a complex relationship with abandonment of treatment. Thus, it follows that strategies to reduce treatment abandonment (and increase a child's chance for survival) must be multidimensional. Conclusions Qualitative studies of how families perceive childhood cancer and treatment can illuminate the processes and relationships involved in abandonment of treatment. This approach can also show how families' living circumstances frame their perceptions and inform strategies to improve how medical services are provided, thus reducing abandonment of treatment.